Tracking translocation of industrially relevant engineered nanomaterials (ENMs) across alveolar epithelial monolayers in vitro. Issue 1 (August 2014) - Cohen, Joel M.; Derk, Raymond; Wang, Liying; Godleski, John; Kobzik, Lester; Brain, Joseph; Demokritou, Philip
Abstract Relatively little is known about the fate of industrially relevant engineered nanomaterials (ENMs) in the lungs that can be used to convert administered doses to delivered doses. Inhalation exposure and subsequent translocation of ENMs across the epithelial lining layer of the lung might contribute to clearance, toxic effects or both. To allow precise quantitation of translocation across lung epithelial cells, we developed a method for tracking industrially relevant metal oxide ENMs in vitro using neutron activation. The versatility and sensitivity of the proposed in vitro epithelial translocation (INVET) system was demonstrated using a variety of industry relevant ENMs including CeO2 of various primary particle diameter, ZnO, and SiO2-coated CeO2 and ZnO particles. ENMs were neutron activated, forming gamma emitting isotopes 141Ce and 65Zn, respectively. Calu-3 lung epithelial cells cultured to confluency on transwell inserts were exposed to neutron-activated ENM dispersions at sub-lethal doses to investigate the link between ENM properties and translocation potential. The effects of ENM exposure on monolayer integrity was monitored by various methods. ENM translocation across the cellular monolayer was assessed by gamma spectrometry following 2, 4 and 24 h of exposure. Our results demonstrate that ENMs translocated in small amounts (e.g. <0.01% of the delivered dose at 24 h), predominantly via transcellular pathways without compromising monolayer integrity or disrupting tight junctions. It was also demonstrated that the delivery of particles in suspension to cells in culture is proportional to translocation, emphasizing the importance of accurate dosimetry when comparing ENM–cellular interactions for large panels of materials. The reported INVET system for tracking industrially relevant ENMs while accounting for dosimetry can be a valuable tool for investigating nano–bio interactions in the future.